Doxetaxel in previously treated non-small cell lung cancer patients: Clinical efficacy and quality of life - Thitiya Sirisinha (2018)
Docetaxel (Taxotere) is one of the most active new generation chemotherapy agents against advanced non-small cell lung cancer (NSCLC). This study aimed to determine the activity, toxicity and impact on the quality of life (QOL) in patients treated with docetaxel after failure with first-line platinum-based combination chemotherapy. Twenty-one patients with advanced NSCLC who had previously received the platinum-containing regimen were treated with docetaxel 75 mg/m 2 every 3 weeks. QOL was assessed at intervals during the treatment period using the Functional Assessment of Cancer Treatment - Lung (FACT-L). Of the 21 patients enrolled, 16 were able to be evaluated for response and 20 were included in the toxicity analysis. The median age was 57 (range, 39-75 years). A median of 3 cycles was given (range, 1-9). Of the 16 evaluatable patients, there was one partial response (6.3%) and 4 with stable disease (25%). The median survival time was 8.1 months and the 1-year survival rate was 25%. Myelosuppression and peripheral neuropathy were the major toxicities. Grade 3/4 neutropenia and paresthesia occurred in 6 patients (30%) and 3 patients (15%), respectively. There was no significant improvement or deterioration in the overall FACT-L, TOI (Trial Outcome Index) and lung cancer symptom scores during the treatment. Symptom improvement was noted, in particular for shortness of breath and weight loss in the majority of patients. It is concluded that docetaxel is a well tolerated secondline treatment for recurrent NSCLC. Of particular importance was that the treatment did not negatively impact the overall quality of life, on the contrary, did palliate some of the lung cancer related dash symptoms in many patients.